PENGUATAN PESANTREN ABUL HASAN AL- ASYARI BANGKALAN MELALUI NILAI-NILAI SANAD KEILMUAN - Hariyanto , Arif (Proceedings of Annual Conference on Community Engagement, 2024)
Pesantren is one of the models of Indonesian education that continues to make a real contribution through da'wah and assistance to the ummah. In its development, Islamic boarding schools have adapted to the needs and changing times, this is evidenced by the opening of various university study programs that were born from the simplicity of pesantren. This includes the Pesantren Salafiyah Syafi'iyah Sukorjeo which is responsible for the birth of higher education, of course, it must maintain the Islamic boarding school values that are the basis for its characteristics. This includes the character of exemplary behavior, physical routines and dhikrs that are carried out into self-identity which is then referred to as ”Sokmana Santre Sokoarajjeh”. Ibrahimy University, which is part of the Pesantren Sukorejo, carries out the process of recognizing Islamic boarding schools in various Islamic boarding schools which institutionally require assistance in various pesantren institutional sectors. Like the Abul Hasan Al-Asyari Islamic Boarding School Bangkalan, which was only established in 2019, has become a mentoring center starting in 2021. This service uses the Asset-based community development (ABCD) method as the right approach for the problems being assisted